Qualitative assessment of innovations in healthcare provision - Ghosh Amit K; Porzsolt Franz; Kaplan Robert M (BMC, 2009)
Abstract Background The triad of quality, innovation and economic restraint is as important in health care as it is in the business world. There are many proposals for the assessment of quality and of economic restraints in health care but only a few address assessment of innovations. We propose a strategy and new structures to standardize the description of health care innovations and to quantify them. Discussion Strategy and structure are based on the assumption that in the early phase of an innovation only data on the feasibility and possibly on the efficacy or effectiveness of an innovation can be expected. From the patient's perspective, benefit resulting from an innovation can be confirmed only in a later phase of development. Early indicators of patient's benefit will be surrogate parameters which correlate only weakly with the desired endpoints. After the innovation has been in use, there will be more evidence on correlations between surrogate parameters and the desired endpoints to provide evidence of the patient benefit. From an administrative perspective, this evidence can be considered in decisions about public financing. Different criteria are proposed for the assessment of innovations in prevention, diagnosis and therapy. For decisions on public financing a public fund for innovations may be helpful. Depending on the phase of innovation risk sharing models are proposed between manufacturers, private insurers and public funding. Summary Potential for patient benefit is always uncertain during early stages of innovations. This uncertainty decreases with increasing information on the effects of the innovation. Information about an innovation can be quantified, categorized and integrated into rational economic decisions.